2018
DOI: 10.1007/s12076-017-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

The regional heterogeneity of household recycling: a spatial-econometric analysis of Swedish plastic packing waste

Abstract: Environmental policy is often formulated at the national level, but the primary responsibilities for policy implementation, monitoring and compliance are often assigned to local actors (e.g., municipalities). This paper investigates the regional heterogeneity of household plastic waste collection among Swedish municipalities, and how collection rates have been influenced by local waste management policies, geographical conditions and socio-economic characteristics. This is achieved by employing spatial econome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Negative correlation with the percentage of the population over 64 years was also observed by Saladie [24]. D'Elia [19], Hage, and Söderholm [8], and Hage et al [25] found no relation between recycling behavior and age.…”
Section: Factors Influencing Recyclable Generationmentioning
confidence: 57%
See 2 more Smart Citations
“…Negative correlation with the percentage of the population over 64 years was also observed by Saladie [24]. D'Elia [19], Hage, and Söderholm [8], and Hage et al [25] found no relation between recycling behavior and age.…”
Section: Factors Influencing Recyclable Generationmentioning
confidence: 57%
“…The authors explained this relation with higher opportunity costs of households with higher education. No statistically significant influence of education on waste sorting was detected Hage et al [25], or by Šauer, Pařízková, and Hadrabová [28] for the Czech Republic.…”
Section: Factors Influencing Recyclable Generationmentioning
confidence: 91%
See 1 more Smart Citation
“…The publications by Miafodzyeva et al [24], Gregson et al [25], and Bonatti [26] study waste sorting among people with an immigration background or ethnic minorities. All other resource recovery studies that were included in this review do not study waste sorting among people with an immigration background per se, but meet the inclusion criteria because information on waste sorting among ethnic groups or immigrants was presented as a byproduct of their objectives [27][28][29][30][31][32][33]. One study considered people with an immigration background in their tables but did not discuss this further in the text [28].…”
Section: Resultsmentioning
confidence: 99%
“…Waste sorting and recycling among people with an immigration background and ethnic minorities were mentioned in studies that were conducted in Italy [26]; Northern Europe and the UK [25]; the UK [30][31][32][33]; the Netherlands [28]; and Sweden [24,27,29]. All these studies used the concept of 'recycling' rather than 'waste sorting'.…”
Section: Resultsmentioning
confidence: 99%